The genre of spiritual autobiography features in the novel by B. L. Pasternak “Doctor Zhivago” - Односум, Наталія Володимирівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2019)
The article deals with realization of the canonical spiritual autobiography genre in the novel by B. L. Pasternak Doctor Zhivago. For the first time the classical canon of spiritual autobiography is embodied in the Confession by St. Augustine. The following genre signs of spiritual autobiography are distinguished: the choice from the series of events only those moments that contributed to the spiritual growth of the hero; focusing not on the external course of events, but on the internal spiritual processes; the moment of insight, spiritual awakening as a plot-compositional pointe, the culmination of the narrative and, accordingly, the turning point of the hero's life. According to the establishment of eternal history that leads to the beginning in the human spirit with Christ`s sacrifice, the theme of the path is revealed in the new Gospel light in spiritual autobiography - as a person’s ascension from the carnal to the spiritual level of consciousness and achievement of “eternal life”. The main genre-forming principle, besides the listed ones, is the moment of insight, spiritual awakening as a plot-compositional pointe of a work that gets multi-level realization in the novel by B. L. Pasternak Doctor Zhivago: on an individual and biographical, historical, eternal, sacral levels. Such a multi-level realization of the moment of spiritual awakening determines the polyphonic and tiered hierarchical organization of the subject component of the story. The architectonic center of the subject component includes hero-author, hero-generation and hero-Christ paradigms. The interrelation of the subject components is based on the model of the symbolic-iconic generalization of being. The artistic detachment from specific prototypes makes Yuri Zhivago and his contemporaries symbolic figures, connecting microcosms. They interact and become parts and symbols of each other and the whole world at this level of generalization.Such complex subject organization contributed to the transformation and modernization of the canon of spiritual autobiography in the novel by B. L. Pasternak “Doctor Zhivago”.